The synthesis and characterization of novel mesomorphic octa- and tetra-alkylthio-substituted lead phthalocyanines and their films - Atilla, Devrim; Gürek, Ayşe Gül; Basova, Tamara V.; Kiselev, Vitaly G.; Hassan, Aseel; Sheludyakova, Liliya A.; Ahsen, Vefa (Elsevier Sci Ltd, 2011)
Two novel mesomorphic octakis and tetrakis (alkylthio)-substituted phthalocyanines of Pb(II) were synthesized and characterized using NMR UV-Vis FT-IR and mass-spectrometry The mesogenic properties of these new materials forming columnar-hexagonal mesophases were studied by differential scanning calorimetry optical microscopy and X-ray diffraction Visible absorption spectroscopy provided evidence of thermally induced molecular reorganization in films IR spectroscopy and density functional theory calculations were used to study the preferential orientation of molecules relative to the substrate surface The intense IR bands in the spectra of the lead phthalocyanines were assigned with the aid of quantum chemical computations The observed increase in the intensity of the out-of-plane modes in the IR spectra correlate with an average preferential edge-on orientation of the molecules on the substrate surface in the film The current-voltage characteristics of films before and after thermal treatment were also measured The results confirmed the film ordering proposed on the basis of the IR and DFT studies (C) 2010 Elsevier Ltd All rights reserved
Keywords: Lead phthalocyanines; Liquid crystals; IR spectroscopy; Thin films